The Association Between the Risk of Hypertensive Disorders of Pregnancy and Folic Acid: A Systematic Review and Meta-Analysis - Yahui Yu; Ximu Sun; Xinrui Wang; Xin Feng (Frontiers Media S.A., 2021)
Purpose: Although folic acid (FA) supplementation has been shown to reduce general cardiovascular risks, its impact on hypertensive disorders of pregnancy (HDP) is unclear. We performed a systematic review and meta-analysis to clarify the association between FA and the risk of HDP (pre-eclampsia (PE) and gestational hypertension (GH)). Methods: PubMed, EmBase, and Cochrane Library were searched up to June 18, 2020, stratified by type of disease, initiation time of FA, form of FA and pre-conception Body Mass Index (BMI). The quality assessment of included studies was evaluated using Newcastle-Ottawa Scale (NOS) for cohort studies and Cochrane Collaboration's Risk of Bias Assessment Tool for randomized controlled trials (RCTs). Between-study heterogeneity was quantified using Cochran's Q-statistic and I2 statistics. Sensitivity analysis was performed by excluding the studies one by one, and publication bias was analyzed using funnel plots. Results: Twenty studies with 359041 patients were identified for inclusion in the meta-analysis which included 3 RCTs and 17 cohort studies. Pooled estimates showed RR of 0.83 (95%CI 0.74-0.93, P=0.0008) for association between low dose FA (LD-FA) and the risk of PE, but LD-FA was not associated with GH (RR 1.05, 95% CI 0.97-1.13, P=0.20). In addition, the results of subgroup analysis showed that post-conception LD-FA had a 31% decreased risk of PE (RR 0.69, 95% CI 0.59-0.80, P<0.00001), and LD-FA in patients with pre-conception BMI<25 kg/m2 had a 32% decreased risk of PE (RR 0.68, 95% CI 0.56-0.81, P<0.0001) Conclusions: LD-FA significantly decreased the risk of PE but not GH, and post-conception LD-FA and pre-conception BMI<25 kg/m2 were considered as protective factors to reduce the risk of PE.